One-Child Policy and the Rise of Man-Made Twins - Wei Huang; Xiaoyan Lei; Yaohui Zhao (Institute for the Study of Labor (IZA), 2014)
This paper investigates how people respond to the distorted incentives of One-Child Policy by examining its impact on twin births in China. The analysis using population census data shows that the One-Child Policy accounts for more than one-third of the increase in twin births since the 1970s. Further investigation finds that the One-Child Policy is associated with a larger birth gap of twins with prior births and greater height difference between twins. These findings suggest that the increase in twin births can partly be explained by parents registering single children as twins in order to avoid the policy violation punishment.
Keywords: J08; J11; J13; 330; twins; one-child policy; China